PENGEMBANGAN MODEL PERMAINAN SEPAK BOLA GAWANG SKOR DALAM PENJASORKES BAGI SISWA KELAS V SEKOLAH DASAR NEGERI 5 TUBANAN KECAMATAN KEMBANG KABUPATEN JEPARA 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to develop and produce a model of learning through play foot-ballgame goal scoring for elementary school. This study is a research method that refers tothe development of models of Borg & Gall development that has been modified,namely: (1) a preliminary investigation and collection of information. (2) Developinitial product form. (3) Evaluation. (4) Revised first product. (5) field t rial (34students). (6) Revised final product. (7) The final result by the field test revision. Thedata was collected using a questionnaire derived from expert evaluation, small grouptesting, and field trials. Data in the form of the assessment of t he quality of products,suggestions for improvement of the product, and the results of the ques-tionnaires bystudents. The data analysis technique used is descriptive percentage to reveal aspects ofpsychomotor, cognitive, and affective student after using the product. From the testresults obtained by the expert evaluation data, expert penjas 80% (good), 80% learningexpert s (good), a small test group 80% (good), and field trials 80% (good). From theavailable data it can be concluded that the model of learning through play footballgoalkeeper scores can be used for st udents of classes V SD Negeri 5 Tubanan Jeparaacceptable because students and produce learning.